(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Many genetic mutations causing severe reduction or defect in GPIIb (CD41) and/or GPIIIa (CD61) receptors in Glanzmann Thrombasthenia (G.T.). Flow cytometry can be used for quantification of these two receptors for diagnosis and further identification of G.T. types which are type I, II and III. Objective: To detect the occurrence of CD41 (GPIIb) and CD61 (GPIIIa) in patients diagnosed with Glanzmann thrombasthenia and to classify them accordingly by flow cytometry. Methods: A descriptive cross sectional study was conducted on 28 patients with G.T. collected from the National Center of Hematology and Children Welfare Teaching Hospital over 5 months from Dec. 2014 to Apr. 2015. Those patients were subjected to all hematological investigations required for the diagnosis of G.T. Glanzmann Thrombasthnia Italian Team Protocol (GLATIT) was used to assess the severity of bleeding in those cases at time of collecting samples after taking clinical information either directly with their full agreement or from their files. Results: Majority of cases were below 20 years of age with male to female ratio 1:1. According to the results obtained by flow cytometry. Majority of cases (86%) were classified as type I. A single case (3%) was found to be of type II whereas type III constituted 11% of the total no. of cases. Family history and consanguinity were found in 79% and 93% of the affected families respectively. Conclusion: Type I is the most common followed by type III then type II. Most cases were mild bleeders followed by moderate then severe bleeders. Platelet function test is essential to diagnose the variant form of G.T. (type III) which reveal a normal or near normal expression of both receptors as detected by flow cytometry. More than one type of G.T. had been found in one family with variable bleeding severity suggesting that more than one mutation can occur in the same family. Keywords: CD41, CD61, Glanzmann thrombosthenia.